Draughtsmen, Botanists and Nature - Nickelsen, Kärin. author. aut Link
IX, 295 p.
Keywords: This book is the first in-depth study of eighteenth-century botanical illustrations, and its findings offer a completely new insight into the working practices of the botanists and scientific draughtsmen of this period. The author describes the different production stages of these illustrations, traces their uses by means of the private correspondence of participants and the documentation of the learned societies and academies, and explores their visual language, with particular emphasis placed on the difficult issue of colour. Finally, and for the first time, the author presents a convincing description of how these botanical illustrations developed, ascertaining the criteria that drove this process, which was arrived at through a careful study of the many copying links that the author discovered existed between images of the same species -- a sophisticated strategy that fulfilled the exacting requirements of eighteenth-century scientific botanical illustrations.